Moderating role of financing decision on the relationship between corporate governance and corporate profitability: Evidence from companies listed in CSE. - Anandasayanan, S. (University of Jaffna, 2024)
Good governance can contribute to better management practices, reduce the risks of fraud or mismanagement which could lead to improved profitability. Financing decisions are the choices a company makes regarding how it raises capital to fund its operations. The aim of this study is to analyze the impact of corporate governance on corporate profitability through moderating role of financing decision. The study sample consists of 208 non-financial companies and focused on data from the years 2015 to 2021. Corporate Governance Index was constructed in this study. The study measures profitability using the Net Profit Ratio. The findings of this study prove the fact that the corporate governance index has a positive impact on the corporate profitability of the listed companies in Sri Lanka. The debt to equity ratio has a negative impact on the Net Profit Ratio. Companies by maintaining optimum debt to equity ratio can reduce the negative impact on corporate profitability. On the contrary, Debt to Equity* CGI has brought about a positive impact on the corporate profitability of listed companies in Sri Lanka. Debt to equity, which is considered as moderating variable has had a great impact on the relationship between corporate governance and corporate profitability. This implies that corporate profitability is enhanced when there is good CG which will also influence the financing decisions of the companies listed in CSE. The agency theory stated that corporate governance with optimum financing decisions improves profitability, in that it mitigates agency conflicts between shareholders, managers, and debt holders.
Keywords: Corporate Governance Practices; Corporate Profitability; Corporate Governance Index; Debt to Equity; Net profit ratio